METAFISIKA KETUHANAN DALAM PANDANGAN KALAM DAN PENGALAMAN RELIGIUS - Iskandar Zulkarnain (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2016)
Kalam, in general, could be stated as a study that focused to examine the central theological doctrines. By studying Kalam, it will give someone convictions based on solid arguments, not easily distracting by the change of time. Theological metaphysics is one of subject matter in Kalam. Metaphysics in Kalam supposed a certain level of understanding towards "God"; that assumed "God" could be understood. The equivocal term such as "being" (wujud) will obscure the understanding to that "being" should be translated to "existence"  (mawjud), as consequence  therefore "God" become "the permanent" (al-tsabit). Inrelation to Kalam, religious experience has a function as a spiritualvision benefactor in Kalam understanding. Profound appreciationthrough heart (dzauq and wijdan) to study of tauhid or Kalam make this study more appreciate and applicate in attitude. For that reason, religious experience is the perfection of study of tauhid from the perspective of religious experience; it is spiritual application from study oftauhid. This writing analyse the theological metaphysics by religious experience that is lack of attention according to the writer.